Investigation of abundant treated sea sand with different percentages in concrete brick ratio 1:3 - Mohd Syahmi Hafiz, Yasin (2010)
The Concrete bricks are usually used extensively in the construction industry as a wall panel, part of the construction of drains and so on. Usually, concrete bricks are using cement and normal sand such as Ordinary Portland Cement and river sand. In addition, the concrete brick also must have its own mix ratio for enabling the content to be a piece of brick. Usually, the use of river sand in our country is very widespread in the construction industry. Therefore, an alternative to use of river sand can be replaced with other materials to protect the environment of the river as well as prevent erosion and flooding. By using the abundant sea sand is one of the alternatives in the investigation of this concrete brick. River sand will be replaced with abundant sea sand in accordance with a specified percentage. The percentage of the abundant sea sand to replace with the river sand is 5%, 10%, 15% and 20%. In addition, a size of concrete brick was determined in this study, the size using is 225mm x 115mm x 75mm. The quantities of concrete bricks was made was 100 pieces and it will be tested in destruction test. The concrete bricks are placed in a water tank for the curing for 7 days and 28 days. Concrete brick was then tested with water absorption tests and compression strength test. These tests were conducted to ensure the quality of material, to reduce the cost and the important thing is to reduce the parties involved from having the problem at the next stages. This investigation shows that by using the abundant treated sea sand as replacing material with sand/cement ratio 1:3 is suitable and also can be used in construction industries.